Online learning during the COVID-19 pandemic: Medical students’ perspective of challenges and barriers - Loma Al-Mansouri; Firas R. Al-Obaidi; Noor Ahmed Abdullah (Medical Journal of Babylon)
Abstract Background: Medical education has been affected significantly during the coronavirus disease (COVID-19) pandemic. During the pandemic, online learning functioned as the principal pathway of education at all levels of education for a considerable time. Online medical education has faced many challenges and constraints. Objectives: To evaluate the students’ perception toward online medical education in Iraq and related challenges and limitations. Materials and Methods: This study is a cross-sectional, descriptive study to evaluate the challenges and barriers of online learning during the COVID-19 pandemic. We created an online questionnaire. The survey was introduced to undergraduate students in the medicine, pharmacy, dentistry, and nursing colleges from all stages at the University of Basrah, south of Iraq. The study was conducted in April 2020. Results: The total number of participants was 882 students. There were 438 (49.6%) females. The responses of the students showed different problems and limitations facing online learning. These were divided into student-, faculty-, and technical-related barriers. The survey showed that 77% of the students are facing difficulties with having internet or having low-quality internet services. In addition, there was a shortage of students’ electronic devices mainly due to financial causes. The faculty-related were considered by the students (71.4%) to be mainly the deficient experience of the teaching staff in using digital resources. The students (49.4%) recommended online learning to continue in the future, blended with a classic education. Conclusion: The perception of medical students toward online learning was positive. The challenges and barriers to online education were related to students, faculty, and technical factors. The role of online learning can be promising in the post-COVID-19 era.